The Effect of Using EDRAAK Educational Platform on the Academic Achievement among Tenth Grade Students and Their Attitudes Towards it - Al-Shugairat, Mohammad Falah; Al-Rsaaie, Mohammad Salameh (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the Effect of Using EDRAAK Educational Platform on the Academic Achievement among the Tenth Graders and Their Attitudes towards It, the sample of the study consisted of (50) students from the tenth grade in the Petra District Education Directorate, who were randomly divided into two groups (experimental and control). The researchers used the quasi-experimental approach, and the study tools consisted of a multiple-choice test of (20) items to measure student achievement, and an attitudes scale consisting of (24) items, and the results of the study showed There were statistically significant differences at the level of significance (α≤0.05) for teaching using EDRAAK platform on the achievement of tenth grade students in basic mathematics, where the value of t = 3.616 and by looking at the average achievement of the members of the two study groups (experimental and control) on the post-test we find that the difference is due to the average achievement of the experimental group students, which reached (10.64), while the average achievement of the control group on the post-test was (7.24). The results also showed that there are statistically significant differences at the significance level (α≤0.05) for teaching using EDRAAK educational platform on the attitudes of the tenth grade basic students towards mathematics, where the value of t = 2.42, and by looking at the average trends of the members of the two study groups (experimental and control) on the post-test (attitudes), we find that the differences between the averages of students attitudes on the post-test are in the interest of the group’s students the experimental group reached (2.89), while the average attitudes of the control group students reached (2.68). The researchers recommend the necessity of adopting educational platforms as an integral part of the education process in the schools of the Hashemite Kingdom of Jordan.